Assessment of the Relationship of Treated Basal-Type Breast Cancer with Recurrence, Metastasis, and Chemotherapy Regimen at A Tertiary Hospital Over Five Years - Sharifi Esfahani , Mehran; Ahmadi, Samaneh; Taatii Moghadam, Mahtab (Novelty in Biomedicine, 2026)
Background: Some studies suggest that basal-type breast cancer is a subtype of triple-negative breast cancer, and some others mention that it is a unique type of breast cancer. There are limited studies on the results of treatment and outcomes of patients with basal-type breast cancers. Therefore, we aimed to assess the relationship of treated basal-type breast cancer with recurrence, metastasis, and chemotherapy regimen. Materials and Methods: This retrospective cohort study analyzed patients with treated basal-type breast cancer at Omid Hospital in Mashhad, Iran, from 2016 to 2020. Data were obtained from the Breast Cancer Registry System, including age at diagnosis, affected side (right or left breast), cancer stage, metastasis, relapse, and chemotherapy regimens. Patients were then contacted to assess their two-year survival outcomes. A significance level of less than 0.05 was considered. Results: Ninety-three patients with a mean age of 47.41 ± 17.16 years were evaluated. Of these, 19 patients (20.4%) presented with metastasis, and 14 patients (15.1%) faced relapse. The two-year survival rate was 74.2%. Age was associated with relapse and metastasis (P-value< 0.01 and 0.03, respectively). Higher tumor stage was associated with increased metastasis (P-value < 0.05). Among patients without relapse, 81.0% survived after two years; among those without metastasis, the survival rate was 86.5%. Chemotherapy type did not show significant associations with metastasis, relapse, age, stage, or survival outcomes (all P-values > 0.05). Conclusion: The administration of chemotherapy, irrespective of its specific type, has demonstrated beneficial effects on basal-type breast cancer.